Factores que influyen en la aparición de flebitis química en pacientes hospitalizados en el área de oncología del Hospital de Especialidades FF.AA. nº1, octubre 2018-abril 2019 - Navarrete Ruiz, Mayra Alejandra (2019)
The investigative study is deepened in an irritation that arises in the vascular endothelium of the vein, the population with the highest risk of developing it, are those that should receive intravenous treatment in different hospital centers. The causes of its development can be: the administration of irritating medications, prolonged infusion time, Improper handling of peripheral vias, among others. The objective of the research is to determine what factors influence in the appearance of chemical phlebitis in hospitalized patients in the oncology area of the Hospital of specialties FF.AA. Nº1, October 2018-April 2019. This research study is cross-sectional, bibliographical and descriptive because it was executed in a period of time from October 2018 to April 2019, collecting information about chemical phlebitis and its factors that influence its development supported by books and scientific journals. The following results were obtained, from the total of 30 patients who were Hospital of specialties FF.AA. Nº1, October 2018-April 2019, which were included in an age of 31-64 years, according to the observation card to assess peripheral catheters during intravenous treatments, 12 patients were obtained who developed chemical phlebitis. It was concluded that the factors that influence the appearance of chemical phlebitis are: irritant chemotherapeutic drugs, the ignorance of nurses in the administration of chemotherapeutic drugs and the insufficient evaluation of the peripheral venous catheter during the administration of chemotherapeutic drugs.